2012
DOI: 10.1089/ten.tea.2011.0187
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Stromal Cell-Derived Factor-1/CXC Chemokine Receptor 4 Axis Enhances rhBMP-2-Induced Ectopic Bone Formation

Abstract: Enhancement of in vivo mobilization and homing of endogenous mesenchymal stem cells (MSCs) to an injury site is an innovative strategy for improvement of bone tissue engineering and repair. The present study was designed to determine whether mobilization by AMD3100 and/or local homing by delivery of stromal cellderived factor-1 (SDF-1) enhances recombinant human bone morphogenetic protein-2 (rhBMP-2) induced ectopic bone formation in an established rat model. Rats received an injection of either saline or AMD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…The existing data from our study and other studies [57,59] document the use of the CXCR4 antagonist, AMD3100, has an effect on bone formation in at least three microenvironments: ectopic, cranial, and appendicular in this model. The concept should therefore be further explored to improve bone regeneration after trauma-or surgical-induced damage to bone.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The existing data from our study and other studies [57,59] document the use of the CXCR4 antagonist, AMD3100, has an effect on bone formation in at least three microenvironments: ectopic, cranial, and appendicular in this model. The concept should therefore be further explored to improve bone regeneration after trauma-or surgical-induced damage to bone.…”
Section: Discussionsupporting
confidence: 60%
“…While the finding at 21 days appears to be a modest increase, Wang et al [57] showed treatment with AMD3100 for 15 continuous days starting 3 days after a critical-size cranial defect was created improved bone healing at 56 and 112 days but not at 28 days. In a recent report from our laboratory, we noted a single injection of AMD3100 enhanced bone volume in a rat model of ectopic bone formation [59]. The effect was observed at 56 days but not at 28 days, although at the earlier time point there was qualitative evidence of active bone formation in the treated animals whereas the control animals already had a relatively well-established marrow compartment.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…24 These in vitro findings were later extended using primary mouse and human bone-marrow-derived mesenchymal stem cells (BMSCs), 25 setting the stage for investigating the BMP-2/SDF-1 interaction employing orthotopic and ectopic bone formation models. [26][27][28][29] Previous studies have suggested that the CXCR4/SDF-1 axis functions in postnatal bone formation by regulating osteoblast development in cooperation with BMP signaling, and that CXCR4 acts as an endogenous signaling component necessary for bone formation. 29 We 30 and others 31 have shown that bone marrow endothelial and stromal cells, and osteoblasts express both major SDF-1 splice variants, and that unexpectedly the beta isoform may be present at a high level in bone tissues.…”
mentioning
confidence: 99%